(untitled) (Indian Journal of Child Health, 2025)
Background: Congenital hypothyroidism (CH) is one of the most common preventable causes of mental retardation (MR). Due to the typically asymptomatic nature of congenital hypothyroidism (CH) in newborns, universal screening is necessary. Cord blood TSH (CB-TSH) levels have good sensitivity. However, many maternal and perinatal factors cause variations in Cord blood TSH levels, which can interfere with interpreting its levels and diagnosis. Aim: This study was done to determine various maternal and perinatal factors affecting CB-TSH levels. Materials and Methods: A cross-sectional study was conducted in the Department of Paediatrics and Neonatology in a Tertiary care centre. Cord blood TSH level was estimated, and the results were statistically analysed concerning various maternal and perinatal factors. A TSH cut-off of >20microIU/ml was considered as high. Results: The median Cord blood-TSH was 7.945microIU/L (Interquartile range = 6.475 – 12.82) with 10% (n=13) of newborns had elevated cord blood TSH levels (>20 microIU/ml). Among them, 2.3%(n=3) of newborns had subclinical hypothyroidism (serum TSH 10-20 microIU/ml, normal FT4). No babies were found to have overt hypothyroidism—requirement of resuscitation, low birth weight, birth asphyxia, and low Appearance, Pulse rate, Grimace, Activity, and Respiratory effort (APGAR) score, maternal (add a comma after APGAR score) diabetes and antenatal complications (other than hypertension/Diabetes (DM)/ hypothyroidism) showed a significant association even on multivariate analysis. Preterm gestation, male gender, and maternal hypothyroidism were significant in univariate analysis. The mean TSH levels found in our study were 11.96 ± 15.01. The correlation between cord blood TSH and 72-hour thyroid profile was found insignificant because of a low number of babies with high cord TSH. Conclusions: Since various maternal and perinatal factors affect the levels of TSH in cord blood, any increase in cord TSH should be interpreted in the context of these circumstances.